CB2 cannabinoid receptor expression is increased in 129S1/SvImJ mice: behavioral consequences - Ten-Blanco, Marc; Pereda-Pérez, Inmaculada; Izquierdo-Luengo, Cristina; Berrendero, Fernando (Frontiers in Pharmacology, 2022)
Genetic and environmental factors are implicated in the etiology of neuropsychiatric diseases. Inbred mouse strains, including the 129S1/SvImJ (S1), constitute important models to study the influence of genetic factors in these conditions. S1 mice displayed anxiogenic-like behavior, impaired fear extinction, and increased prepulse inhibition (PPI) of startle reflex compared to C57BL/6J (BL6) mice. Given the role played by the endocannabinoid system (ECS) in these responses, we evaluated the expression of the ECS components in different brain regions in S1 mice. Gene expression levels of the cannabinoid type-1 and type-2 receptors (CB1R and CB2R) and the endocannabinoid metabolizing enzymes varied depending on the brain region evaluated. Notably, CB2R expression markedly increased in the amygdala, prefrontal cortex and hippocampus in S1 mice. Moreover, CB2R blockade with SR144528 partially rescued the anxiogenic phenotype in S1 mice, while CB2R activation with JWH133 potentiated the deficits in fear extinction and the PPI of startle reflex in this mouse strain. These data suggest that CB2R is involved in the behavioral alterations observed in S1 mice and underline the importance of this cannabinoid receptor subtype in the regulation of certain central nervous system disorders.